2005
DOI: 10.3748/wjg.v11.i11.1599
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diffusion in gel entrapment cell culture within hollow fibers

Abstract: Cell-matrix gel and membrane pore size are the two factors relevant to the limited mass transfer by diffusion in such gel entrapment of mammalian cell culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 30 publications
4
34
0
1
Order By: Relevance
“…This decrease could probably be attributed to nutrient limitation, accumulation of toxic metabolites or diffusion limitation in the gel matrix. 56,57 Second, when the cytotoxicity data collected, after 3 h of exposure to toxin or whole bacterial cells, showed lower cytotoxicity value when compared with 6 h postinfection values (Figure 3a). It was also observed that the cytotoxicity values were slightly lower but not statistically significant in 3D collagen-entrapped assay format as compared to 2D control without collagen (Figure 5a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease could probably be attributed to nutrient limitation, accumulation of toxic metabolites or diffusion limitation in the gel matrix. 56,57 Second, when the cytotoxicity data collected, after 3 h of exposure to toxin or whole bacterial cells, showed lower cytotoxicity value when compared with 6 h postinfection values (Figure 3a). It was also observed that the cytotoxicity values were slightly lower but not statistically significant in 3D collagen-entrapped assay format as compared to 2D control without collagen (Figure 5a).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the slower diffusion of toxin molecules or released enzymes and substrates in the gel as compared to the liquid system. 57 Moreover, the gel matrix sieve size is a limiting factor for bacterial entry (Figure 5b). The requirement of a longer postinfection incubation time with intact bacterial cells, and the lower concentrations of detectable ALP may be attributed to a collagen concentration, which may hinder bacterial passage in the gel matrices and to reach to hybridoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus in this paper the contribution of cells (by taking into account seeding cell density as well as cell activity) on mass transfer resistance was studied. Further, the increased reduction of the diffusivity in loading with viable cells than with dead cells illustrated the negative contribution of contraction alone (Wu et al 2005). As a result, when cell densities were fixed in gel entrapment culture, increasing collagen concentrations could trigger two counteractive impacts on mass transfer: reducing mass transfer across collagen; enhancing mass transfer due to less severe gel contraction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the entrapment of bacterial or mammalian cells in gel obviously inhibits mass transfer by decreasing the diffusivity as a result of enhanced tortuosity (Mateus et al 1999;Nicholson and Phillips 1981;Nicholson and Sykova 1998). As the embedded viable cells mentioned above possibly exacerbate the reduced diffusivity, our previous entrapment of dead cells without causing contraction could better reflect the contribution of cells alone to the reduced diffusivity (Wu et al 2005). Thus in this paper the contribution of cells (by taking into account seeding cell density as well as cell activity) on mass transfer resistance was studied.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on glucose diffusion through gels calculate these delays using lag-time analysis, where the delay is the x intercept from a linear fit of total glucose diffusion through the gel membrane over time. [21][22][23] In the case of our sensors, fluorescence response is related to glucose concentration, and therefore the x intercept of the linear fluorescence response was used for delay calculations. For gel 1, the gel coating caused a lag time for initiating sensor response by 0, 16, and 19 min for the ratios 5:1, 2:1, and 1:1, respectively.…”
Section: In Vitro Characterizationmentioning
confidence: 99%